2018
DOI: 10.3892/ol.2018.9317
|View full text |Cite
|
Sign up to set email alerts
|

Association between IDH1/2 mutations and brain glioma grade

Abstract: Isocitrate dehydrogenase 1/2 (/2 mutations are frequently detected in glioma. The aim of the present study was to investigate the association between /2 mutations and glioma grades. The current study was retrospective and used samples from 206 patients with brain glioma and 9 patients with spinal cord glioma as a control. Patients were diagnosed and graded according to the World Health Organization classification of tumors of the central nervous system. The association of patient age with glioma grade was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 29 publications
3
44
0
Order By: Relevance
“…Subsequently we sought to assess the frequency of IDH1/2 mutation, 1p/19q co-deletion status and other pathological features with respect to proliferation rate of cultured gliomas. In accordance with several previous reports (29,30), IDH1/2 mutations were essentially found among grade II with negligible association to proliferation rate. Similarly MIB1 expression were found exclusively in the high-grade, but not in low-grade, irrespective of proliferation status of glioma cultures.…”
Section: Discussionsupporting
confidence: 93%
“…Subsequently we sought to assess the frequency of IDH1/2 mutation, 1p/19q co-deletion status and other pathological features with respect to proliferation rate of cultured gliomas. In accordance with several previous reports (29,30), IDH1/2 mutations were essentially found among grade II with negligible association to proliferation rate. Similarly MIB1 expression were found exclusively in the high-grade, but not in low-grade, irrespective of proliferation status of glioma cultures.…”
Section: Discussionsupporting
confidence: 93%
“…No patients with ependymoma showed this mutation. Previous studies have indeed shown the association of IDH1 mutation with histology and grading of gliomas (Yan et al, 2009;Qi et al, 2014;Yusoff et al, 2016;Wang et al, 2016;Deng et al, 2018). The percentage of oligodendroglioma samples with IDH1 mutation in our study is quite similar to those in previous studies (Mukasa et al, 2012;Senhaji et al, 2016;Wang et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, we propose a novel radiomics set by using F-score feature selection. Moreover, because IDH1 mutation is related to drug response of GBM [14,15], here, we compare the MGMT status in IDH1 wildtype mutation by using a highly efficient radiomics feature set and advanced machine learning techniques.…”
Section: Introductionmentioning
confidence: 99%